(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this research, we propose a Healthy Life Analysis Model tailored for aging populations, utilizing Long Short-Term Memory (LSTM) networks, a sophisticated type of Recurrent Neural Network (RNN).